2016
DOI: 10.15376/biores.11.2.4885-4898
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Protein A Immobilized on Cross-linked Cellulose Microspheres for Immunoglobulin G Adsorption from Human Plasma

Abstract: Cross-linked cellulose microspheres (CL-CMs) were successfully prepared using an inverse crosslinking suspension method from a cellulose solution with sodium hydroxide/urea aqueous solution as a solvent and epichlorohydrin as the crosslinker. The effects of epichlorohydrin content on the appearance and dispersity, average pore volume, moisture content, and wet real density of CL-CMs were studied. The microspheres presented a good spherical shape and porous surface structure. After activation with NaIO4, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…This has been achieved due to the site-specific reaction, which is an undoubtful advantage when compared to other chemical immobilization methods. Thus, the application of some nonspecific chemical methods frequently results in the formation of resins with dynamic capacity which do not exceed 13 mg/mL [16]. Alternatively, Wang and co-authors demonstrated that the introduction of the glutaraldehyde as an additional linker and a change in the immobilization conditions can alter to some extent the protein orientation on the matrix and increase DBC 10 values (up to 45 mg of IgG per 1 mL of the resin) in resulting resins [17].…”
Section: Characterization Of Affinity Resin Ementioning
confidence: 99%
“…This has been achieved due to the site-specific reaction, which is an undoubtful advantage when compared to other chemical immobilization methods. Thus, the application of some nonspecific chemical methods frequently results in the formation of resins with dynamic capacity which do not exceed 13 mg/mL [16]. Alternatively, Wang and co-authors demonstrated that the introduction of the glutaraldehyde as an additional linker and a change in the immobilization conditions can alter to some extent the protein orientation on the matrix and increase DBC 10 values (up to 45 mg of IgG per 1 mL of the resin) in resulting resins [17].…”
Section: Characterization Of Affinity Resin Ementioning
confidence: 99%